378 RAGE Ablation Attenuates Glioma Progression and Enhances Tumor Immune Responses by Suppressing Galectin-3 Expression. (April 2023) - Dayyani, Mojtaba; Zhang, Ian; Liu, Shunan; Zhang, Leying; Liang, Rongrui; Fang, Qinxiao; Zhao, Jie; Ren, Lyuzhi; Medina, Eric; Filippov, Aleksandr; Bonjoc, Kimberley-Jane; Chaudhry, Ammar; et al.
Abstract : INTRODUCTION: Malignant gliomas consist of heterogenous cellular components that have adopted multiple overlapping escape mechanisms that overcome both targeted and immune-based therapies. The receptor for advanced glycation end products (RAGE) is a member of the immunoglobulin superfamily that is activated by diverse proinflammatory ligands present in the tumor microenvironment (TME). Activation of RAGE by its ligands stimulates multiple signaling pathways that are important in tumor growth, invasion, and immune escape. METHODS: We evaluated genetic ablation of RAGE on the tumorigenicity of two syngeneic murine glioma models. RAGE expression was inhibited in the GL261 and K-Luc gliomas by shRNA and CRSPR/Cas9 techniques prior to intracranial implantation. Tumor growth, invasion, and inflammatory responses were examined by immunohistochemistry, qPCR, ELISA, western blotting, NanoString, flow cytometry, and in vivo survival analysis. RESULTS: Intracellular RAGE ablation abrogated glioma growth and invasion by suppressing AKT and ERK1/2 activities and by downregulating MMP9 expression. Interestingly, RAGE inhibition also enhanced tumor inflammatory responses by downregulating the expression of galectin-3, rendered the immunotherapy resistant K-Luc gliomas responsive to immune checkpoint blockade therapy, and significantly increased survival. CONCLUSIONS: This study is the first to link RAGE expression with galactin-3 as an immune modulator in glioblastoma and revealed that the effect of glioma RAGE expression on TME was mediated through downregulation of Gal-3 and subsequent polarization of Tumor-associated macrophages. The therapeutic significance of RAGE downregulation was demonstrated by sensitizing a highly invasive and immune-resistant glioma model to immune checkpoint blockade and strongly supports the development of RAGE ablation as a complementary treatment strategy for malignant gliomas.